Solve the equation
- 1
- m - 7 = 5
3

Answers

Answer 1
Answer:

1/3m-7=5

One solution was found :

m = 36
Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

1/3*m-7-(5)=0

Step by step solution :

Step 1 :

1
Simplify —
3
Equation at the end of step 1 :

1
((— • m) - 7) - 5 = 0
3
Step 2 :

Rewriting the whole as an Equivalent Fraction :

2.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

7 7 • 3
7 = — = —————
1 3
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

m - (7 • 3) m - 21
——————————— = ——————
3 3
Equation at the end of step 2 :

(m - 21)
———————— - 5 = 0
3
Step 3 :

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

5 5 • 3
5 = — = —————
1 3
Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(m-21) - (5 • 3) m - 36
———————————————— = ——————
3 3
Equation at the end of step 3 :

m - 36
—————— = 0
3
Step 4 :

When a fraction equals zero :

4.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.

Here's how:

m-36
———— • 3 = 0 • 3
3
Now, on the left hand side, the 3 cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :
m-36 = 0

Solving a Single Variable Equation :

4.2 Solve : m-36 = 0

Add 36 to both sides of the equation :
m = 36

One solution was found :

m = 36

I happen this help

Related Questions

What is the value of 3 1⁄4 increased by 2 1⁄6?
50 testers can complete 25 test cases in 10 days. All testers are equally productive. A project has 25 testers and 50 test cases. How much time will they take to complete?
Sam baked 6 cupcakes less than Michelle. Sam baked 18 cupcakes. Which equation will tell you how many cupcakes Michelle baked?
The figure has line(s) of symmetry. What type(s) of symmetry does the figure have?
There is an average of 3.5×10−2 kilograms of dissolved salt in each liter of seawater. The South China Sea contains approximately ​ 9.88×1018 ​ liters of seawater. How many kilograms of dissolved salt are in the South China Sea? Enter your answer, in scientific notation, in the boxes.

The number of potholes on 30 randomly selected 1 mile stretch of highways in the City of Chicago is given below 2, 7, 4, 7, 2, 7, 2, 2, 2, 3, 4, 3, 1, 2, 3, 2, 1, 4, 2, 2, 5, 2, 3, 4, 4, 1, 7, 6, 3, 5 (a) Complete the frequency distribution for the data. Make sure to enter your answers for the relative frequency as decimals, rounded to the nearest tenth.

Answers

Answer:

Kindly check explanation

Step-by-step explanation:

Given the data:

2, 7, 4, 7, 2, 7, 2, 2, 2, 3, 4, 3, 1, 2, 3, 2, 1, 4, 2, 2, 5, 2, 3, 4, 4, 1, 7, 6, 3, 5

Value __ Frequency ___ relative frequency

1 ___ 3 ______ 3/30 ____ 0.1

2 __ 10 ______ 10/30 ___ 0.3

3 __ 5 _______ 5/30____0.2

4 __ 5 ________ 5 / 30 __0.2

5 __ 2 _________ 2/30 __ 0.1

6 __ 1 _________ 1/30 ___0.0

7 __ 4 ________ 4/30 ___0.1

Kindly note that relative frequencies were rounded to the nearest tenth.

WILL GIVE BRAINLIEST IF CORRECT!!How many different 7-digit positive integers exist? (Note that we don't allow "7-digit" integers that start with 0, such as 0123456; this is actually a 6-digit integer.)

Answers

Answer:

There are 9,000,000 seven-digit positive integers.

Explanation:

For the first digit, we have 9 choices: 1, 2, 3, 4, 5, 6, 7, 8, 9.

For each remaining digit, we have 10 choices: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9.

Each choice is independent of the others. So, the number of total 7-digit positive integers is the product of all the numbers of choices for each digit.

hope it helps

need brainliest......

Since 0 cannot be put as the first digit, there are 9 choices for the first digit, and the next 6 digits have 10 choices. So, there are 9 × 10^6 = 9000,000 numbers.  

Help pls with answer!!!Rewrite the function in the given form.

Answers

Answer:

g(x) = (-2)/(x-1)+5\n\n

The graph is shown below.

=========================================================

Explanation:

Notice that if we multiplied the denominator (x-1) by 5, then we get 5(x-1) = 5x-5.

This is close to 5x-7, except we're off by 2 units.

In other words,

5x-7 = (5x-5)-2

since -7 = -5-2

Based on that, we can then say,

g(x) = (5x-7)/(x-1)\n\ng(x) = (5x-5-2)/(x-1)\n\ng(x) = ((5x-5)-2)/(x-1)\n\ng(x) = (5(x-1)-2)/(x-1)\n\ng(x) = (5(x-1))/(x-1)+(-2)/(x-1)\n\ng(x) = 5+(-2)/(x-1)\n\ng(x) = (-2)/(x-1)+5

This answer can be reached through alternative methods of polynomial long division or synthetic division (two related yet slightly different methods).

-------------------------

Compare the equation g(x) = (-2)/(x-1)+5\n\n to the form g(x) = (a)/(x-h)+k\n\n

We can see that

  • a = -2
  • h = 1
  • k = 5

The vertical asymptote is x = 1, which is directly from the h = 1 value. If we tried plugging x = 1 into g(x), then we'll get a division by zero error. So this is why the vertical asymptote is located here.

The horizontal asymptote is y = 5, which is directly tied to the k = 5 value. As x gets infinitely large, then y = g(x) slowly approaches y = 5. We never actually arrive to this exact y value. Try plugging in g(x) = 5 and solving for x. You'll find that no solution for x exists.

The point (h,k) is the intersection of the horizontal and vertical asymptote. It's effectively the "center" of the hyperbola, so to speak.

The graph is shown below. Some points of interest on the hyperbola are

  • (-1,6)
  • (0,7) .... y intercept
  • (1.4, 0) .... x intercept
  • (2, 3)
  • (3, 4)

Another thing to notice is that this function is always increasing. This means as we move from left to right, the function curve goes uphill.

Working together, two secretaries can stuff the envelopes for a political fund-raising letter in 4 hours. Working alone, it takes the slower worker 6 hours longer to do the job than the faster worker. How long does it take each to do the job alone

Answers

Answer: The faster one needs 6 hours, the slower one needs 12 hours.

Step-by-step explanation:

Let's define Sa and Sb as the times that each worker needs to stuff the envelopes for a political fundraising letter.

Sa is the faster one

Sb is the slower one.

Let's define 1 as a complete task.

Then:

when they both work together, they need 4 hours:

(1/Sa + 1/Sb)*4h = 1.

The slower one needs 6 more hours than the faster one:

Sb = (Sa + 6h).

We can replace this in the first equation and get:

(1/Sa + 1/(Sa + 6h))*4h = 1.

let's solve this for Sa.

1/Sa + 1/(Sa + 6h) = 1/4h.

(Sa + 6h) + Sa = Sa*(Sa + 6h)/4h.

2*Sa + 6h = Sa^2/4h + Sa*(6/4)

Then we have a quadratic equation:

(1/4h)*Sa^2 - (2/4)*Sa - 6h = 0h

(0.25*1/h)*Sa^2 - 0.5*Sa - 6h = 0h

The solutions come from the Bhaskara equation:

Sa = (0.5 +- √((0.5)^2 - 4*0.25h*(-6)) )/(2*0.25* 1/h)  = (0.5 +- 2.5)/(0.5) h

Then we have two solutions:

Sa = ((0.5 + 2.5)/0.5 )h = 6h.

Sb = ( (0.5 - 2.5)/0.5) = -4h

The one that makes sense is the positive option (the negative one has no physical meaning in this situation)

Then the faster worker needs 6 hours to stuff all the envelopes.

And the slower one needs 6h + 6h = 12hours to stuff all the envelopes.

So when they work together, the combined rate is:

(1/6h + 1/12h) = (2/12h + 1/12h) = (3/12h) = (1/4h)

So working together they need 4 hours to stuff all the envelopes.

Given m< BAD= y and m

Answers

Answer:

y = 22

Step-by-step explanation:

Consecutive Angles of a parallelogram are supplementary

y + 4y -70 = 180

5y - 70 = 180

5y = 110

y = 22

One thousand tonnes (1000 t, one t equals 10 cubed kg) of sand contains about a trillion (10 super 12) grains of sand. How many tonnes of sand are needed to provide 1 mol of grains of sand? (b) Assuming the volume of a grain of sand is 1.0 mm3 and the land area of the continental United States is 3.6 multiplication 10 super six square miles, how deep would the sand pile over the United States be if this area were evenly covered with 1.0 mol of grains of sand?

Answers

Answer with Step-by-step explanation:

Since 1 mole of sand will contain Avagadro's Number of sand particles (by definition of 1 mole)

Thus we have

1 mole of sand = 6.022* 10^(23) sand particles

Thus in number of trillion sand particles we have no of trillion sand particles in 12 mole is

(6.022* 10^(23))/(10^(12))=6.022* 10^(11)

Now since it is given that mass of 1 trillion sand particles is 1000 tonnes Thus the mass of 6.022* 10^(11) trillion sand particles is

Mass=1000* 6.022* 10^(11)=6.022* 10^(14)tonnes

Part 2)

Since it is given that volume of 1 sand particle is 1.0mm^(3) thus the volume of 1 mole of sand is volume of 6.022* 10^(23) sand particles

Thus volume of 1 mole is V=1.00* 10^(-18)km^(3)* 6.022* 10^(23)=6.022* 10^(5)km^(3)

Now since the Area of united states is A=3.6* 10^(6)mile^(2)=5.8* 10^(6)km^(2)

Thus the depth of the sand pile is

Depth=(Volume)/(Area)=(6.022* 10^5)/(5.8* 10^6)=0.10387km=103.8meters